Reduction of Hot-Spot on Solar PV Array Due to Partial Shading Condition - Baharin, Nur Iman; Yahaya, Jabbar Al-Fattah; Ahmad, Md. Zarafi (Evolution in Electrical and Electronic Engineering, 2024)
Photovoltaic (PV) solar technology encounters issues with partial shading, resulting in hotspots. Conventional solutions, such as cooling systems, prove inadequate. Maximum Power Point Tracking (MPPT) systems offer a superior solution by dynamically adjusting solar panels to alleviate shade-induced inefficiencies. This advanced technology enhances overall efficiency and prolongs the life of solar panels, presenting a promising solution for sustainable energy. While understanding MPPT’s complexities is imperative for integration, its adaptability positions it as a creative and effective tool in the quest for robust renewable energy solutions, addressing challenges associated with partial shading in PV solar systems.